Systematic Literatur Review : Software Matematika MatLab Sebagai Media Belajar untuk Meningkatkan Kemampuan Komputasi Siswa - Afifah Nabila Nasution; Yahfizham Yahfizham (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
MatLab Matrix Laboratory mathematics software is a platform with a programming language created with the aim of being a tool for complex calculations or simulating a system that you want to simulate. This literature study aims to find out whether MatLab mathematics software as a learning medium can improve students' computing abilities through a review of related literature studies. The research method used is a Systematic Literature Review with literature sources used from 2020-2024 and relevant to the research topic. Researchers analyzed thoroughly so that 9 main articles were taken for comprehensive analysis. The results of this SLR research show that MatLab mathematics software as a learning medium can improve students' computing abilities.